2006
DOI: 10.3748/wjg.v12.i11.1747
|View full text |Cite
|
Sign up to set email alerts
|

Roles of adipocyte derived hormone adiponectin and resistin in insulin resistance of type 2 diabetes

Abstract: Plasma adiponectin and resistin are associated with the disorder of metabolism of glucose and lipid in diabetes. The relationship between these hormone and insulin sensitivity suggests that they may take part in the development of insulin resistance of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 27 publications
6
28
0
1
Order By: Relevance
“…As expected, adiponectin and leptin were correlated with L/A ratio negatively and positively, respectively. Resistin is another protein secreted by adipocytes and leads to insulin resistance in vitro and in vivo, constituting a possible link between obesity and diabetes (28). In the present study, we found markedly higher serum resistin levels in T2DM patients compared to controls.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As expected, adiponectin and leptin were correlated with L/A ratio negatively and positively, respectively. Resistin is another protein secreted by adipocytes and leads to insulin resistance in vitro and in vivo, constituting a possible link between obesity and diabetes (28). In the present study, we found markedly higher serum resistin levels in T2DM patients compared to controls.…”
Section: Discussionsupporting
confidence: 65%
“…There were no correlations with age, DM duration, glucose, insulin and HbA1c levels (28,29). Hyperresistinemia would contribute to the pathogenesis of hypertension in patients with T2DM (31).…”
Section: Discussionmentioning
confidence: 83%
“…Decreased adiponectin levels in type 2 diabetes may be one of the reasons to cause insulin resistance [23]. The HOMA model is used to quantify insulin resistance and beta-cell function from fasting plasma insulin and glucose concentrations [24].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, serum resistin strongly correlated with rat insulin sensitivity and resistin was positively correlated with insulin, suggesting that insulin could not inhibit resistin secretion in vivo. A number of factors can regulate resistin secretion, such as glucose, epinephrine, and somatropin [27,30] . Therefore, insulin may regulate resistin although it is not the major regulator.…”
Section: Discussionmentioning
confidence: 99%